Exchange-traded derivatives - Banks, Erik. (Hoboken, N.J. : Wiley, 2003)
This book serves as an ideal resource on the 21st century listed derivative markets, products and instruments.Divided into three parts, Exchange-Traded Derivatives begins by providing an overall understanding of the marketplace and the forces that have, and are, altering the operating environment - stressing how exchanges need to change in order to cope with the challenges. The author then provides a comprehensive description of leading established exchanges, detailing their origins and structure, range of products and services, strengths and 'weaknesses'. The book concludes with a look at emerging marketplaces - those in developing countries as well as new "electronic" platforms - that are likely to increase in importance over the coming years.Exchange-Traded Derivatives is a valuable reference for fund managers, corporate treasurers, corporate risk managers, CFOs and those seeking a detailed guide to the world's derivative exchanges and products.
Includes bibliographical references (p. [233]-235) and index.
rpm 14/05/13
Loans
Keywords: Derivative securities